2020
DOI: 10.3390/rs12040633
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Segmentation Using Deep Learning with Vegetation Indices for Rice Lodging Identification in Multi-date UAV Visible Images

Abstract: A rapid and precise large-scale agricultural disaster survey is a basis for agricultural disaster relief and insurance but is labor-intensive and time-consuming. This study applies Unmanned Aerial Vehicles (UAVs) images through deep-learning image processing to estimate the rice lodging in paddies over a large area. This study establishes an image semantic segmentation model employing two neural network architectures, FCN-AlexNet, and SegNet, whose effects are explored in the interpretation of various object s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(76 citation statements)
references
References 28 publications
0
75
0
1
Order By: Relevance
“…In the future, the proposed VGI setup can be promoted through the execution of street-monitoring techniques to supply long-term continuous imagery; these images, acquired by smartphone cameras, can then be incorporated into Google Street View to construct and update local spatial information. Eventually, by employing more deep learning techniques with distribution computation [63], a great amount of VGI photos can be processed and integrated into a disaster-monitoring system for flooding and traffic management in an economical and time-efficient manner.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, the proposed VGI setup can be promoted through the execution of street-monitoring techniques to supply long-term continuous imagery; these images, acquired by smartphone cameras, can then be incorporated into Google Street View to construct and update local spatial information. Eventually, by employing more deep learning techniques with distribution computation [63], a great amount of VGI photos can be processed and integrated into a disaster-monitoring system for flooding and traffic management in an economical and time-efficient manner.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [8] explored two neural network-based deep learning algorithms to segment color images collected using an unmanned aerial vehicle (UAV) for identifying lodged rice fields. The methodology and results described in their paper indicated that deep learning-based image segmentation (classification) outperformed the conventional Maximum Likelihood method, not only with a higher accuracy but also being 10 to 15 times faster.…”
Section: Machine Learning For Close-range Photogrammetry and Image Anmentioning
confidence: 99%
“…Currently, several attempts have been made to use Deep Learning Neural Networks (DLNN) for the classification of herbs [86][87][88][89][90][91][92][93][94][95][96][97][98][99], and plants diseases [100][101][102][103][104][105][106][107]. The motivation is to attract attention to such methods after the state-of-the-art processing of natural images [84,85].…”
Section: Introductionmentioning
confidence: 99%